Рождение Авроры: роман / Д. Стоун: пер. с англ. - Стоун Диана ("Панорама романов о любви", 2009)
Экземпляры: ф.4 (20150420) / Инвентарный номер: 51565 / Цена: 20. 00. / Сис.шифр: И(4Вел) / Авт.знак: С 82 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44